La défaillance étatique: un paradigme utile pour le dilemme de conflit (Revue El-Wahat pour les Recherches et les Etudes, 2015)
Over a billion and a half people are affected by conflict and fragility, and about 70% of fragile states have suffered from conflict since 1989.The recrudescence of conflicts has brought the issue of the link between conflict and fragile / failed states at the heart of debate ,both at the university and in the international political discourse.This alleged relationship between the two will be the starting point which then seek to analyze the failed state phenomenon on a few points:- The challenges of conceptualization.- Failed state approaches.- International visions and responses to situations of conflict and fragility.- The correlation between conflict and state failure. Keywords: conflict, states, failed states, state failure, situations of conflict and fragility.